Exploring Changes in Musical Behaviors of Caregivers and Children in Social Distancing During the COVID-19 Outbreak - Ribeiro, Fabiana Silva; Braun Janzen, Thenille; Passarini, Luisiana; Vanzella, Patrícia (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has had profound effects on all aspects of society. Families were among those directly impacted by the first measures imposed by health authorities worldwide to contain the spread of the Sars-CoV-2 virus, where social distancing and mandatory quarantine were the main approaches implemented. Notably, little is yet known about how social distancing during COVID-19 has altered families' daily routines, particularly regarding music-related behaviors. The aim of this study was twofold: i) to explore changes in families’ daily routine and caregivers’ levels of well-being and stress during the COVID-19 outbreak in Brazil and ii) to investigate whether musical behaviors of caregivers and the children under their care (aged from 3 to 6 years old) changed during social distancing. One hundred and eighty-eight caregivers residing in Brazil participated in an online cross-sectional study conducted between July and August 2020. Our findings suggest significant changes in families’ dynamics during the COVID-19 outbreak, with parents (especially mothers) spending more time on childcare and a substantial decrease in caregiver’s well-being. Regarding music-related behaviors, our results revealed considerable changes in caregivers’ and children’s musical activities at home during social distancing, including an increase in child-only musical behaviors and shared caregiver-child activities. Moreover, sociodemographic factors such as caregiver background and well-being as well as the child’s disability status significantly influenced musical engagement at home during social distancing. This study captured some features of the home musical environment of middle-class families in Brazil in the first stages of social distancing restrictions during the pandemic and the role of caregivers in providing an environment where musical experiences are nurtured. Further research is needed to better understand aspects such as the long-term impact of the changes in musical behaviors at home on musical parenting and families’ well-being.